Calling all archaeologists: guidelines for terminology, methodology, data handling, and reporting when undertaking and reviewing stable isotope applications in archaeology. (8th February 2018) - Roberts, Patrick; Fernandes, Ricardo; Craig, Oliver E.; Larsen, Thomas; Lucquin, Alexandre; Swift, Jillian; Zech, Jana
Abstract: Stable isotope analysis has been utilized in archaeology since the 1970s, yet standardized protocols for terminology, sampling, pretreatment evaluation, calibration, quality assurance and control, data presentation, and graphical or statistical treatment still remain lacking in archaeological applications. Here, we present recommendations and requirements for each of these in the archaeological context of: bulk stable carbon and nitrogen isotope analysis of organics; bulk stable carbon and oxygen isotope analysis of carbonates; single compound stable carbon and nitrogen isotope analysis on amino acids in collagen and keratin; and single compound stable carbon and hydrogen isotope analysis on fatty acids. The protocols are based on recommendations from the Commission on Isotopic Abundances and Atomic Weights of the International Union of Pure and Applied Chemistry (IUPAC) as well as an expanding geochemical and archaeological science experimental literature. We hope that this will provide a useful future reference for authors and reviewers engaging with the growing number of stable isotope applications and datasets in archaeology.